2000
DOI: 10.1002/1097-0010(200006)80:8<1169::aid-jsfa614>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irradiation on respiration and ethylene production of apple slices

Abstract: Respiration and ethylene production rates of irradiated apple slices from four apple cultivars were measured for 72 h. Doses less than 1.2 kGy had no effect on rates of CO 2 production and O 2 consumption, and irradiation at doses between 1.2 and 2.4 kGy had minimal effect for all cultivars. Respiratory response of `Idared', `Law Rome' and `Empire' slices to irradiation was curvilinear, with maximum respiration occurring in the 3±6 kGy dose range. Response of `Delicious' slices was linear over the irradiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 12 publications
3
7
0
5
Order By: Relevance
“…Papaya is a popular tropical fruit; and the Formosa variety reaches a weight of 2 kg, requiring preparation before consumption. Combinations of several innovative processes can extend the product shelf life, ensuring its final quality (Gunes et al . 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Papaya is a popular tropical fruit; and the Formosa variety reaches a weight of 2 kg, requiring preparation before consumption. Combinations of several innovative processes can extend the product shelf life, ensuring its final quality (Gunes et al . 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Softening of apple structures are associated with changes in pectin composition. After the irradiation process, higher water‐soluble and lower oxalate soluble pectin contents were observed (Gunes, Watkins, & Hotchkiss, ). Similar results were reported by Fan, Niemera, Mattheis, Zhuang, and Olson (), who reported that irradiation at 1 kGy significantly reduced microflora population throughout 21‐day storage period; however, it also reduced fruit firmness and caused browning.…”
Section: Interventions To Reduce L Monocytogenes In Fresh Produce Pamentioning
confidence: 99%
“…Recientemente, la irradiación se ha propuesto como una herramienta para prevenir la contaminación microbiana en una gran variedad de alimentos frescos y procesados (Gunes et al, 2000) demostrándose que la aplicación de dosis relativamente bajas de radiaciones gamma es una herramienta potencial para alargar la vida de poscosecha de muchas frutas y vegetales frescos (Skou et al, 1974;Thomas, 1988;Lescano, 1994;Gautam et al, 1998;Beaulieu et al, 1992Beaulieu et al, y 1999Benoît et al, 2000).…”
Section: Irradiaciónunclassified
“…Chervin et al (1992), encontraron que la irradiación redujo la TR y la producción de etileno en zanahorias. En el caso de la manzana, Gunes et al, (2000) observaron que la irradiación de las láminas de manzana en dosis superiores a 1.2 kGy aumentó la tasa respiratoria y disminuyó la producción de etileno. Sin embargo, la estimulación de la tasa de respiración disminuyó después de 72 h de la irradiación, y por tanto, a largo plazo, los efectos de la irradiación en las tasas metabólicas podrían ser mínimos.…”
Section: Irradiaciónunclassified